Management Model of Lakes as a tool for planning the remediation of Suat Uğurlu Lake - Bilge Aydın Er; Tolga Ayeri; Fulya Aydın Temel; Nurdan Gamze Turan; Yüksel Ardalı (Turkish Journal of Agriculture: Food Science and Technology)
Ecological processes that occur in a lake depend on the physico-chemical (abiotic) and biotic factors of the system and the interrelations between them. It can be concluded that the current nutrient loadings from both point and non-point sources are cause to increase eutrophic case over the years. This study indicate that the sustainable utilization of reservoir in combination with proper wastewater treatment plant and controlled use of pesticides has a potential to reduce the current nutrient loadings into Suat Uğurlu Lake. The estimated nutrient reductions that could be achieved from the management scenario would be enough to revert the lake from mesotrophic situation to trophic state. The reduction of nutrient loadings into Suat Uğurlu Lake could be achieved through the practice of Integrated Water Resource Management (IWRM), through good management. However, as long as pertinent issues of urban poverty, watershed management and public awareness and involvement in water related issues are not addressed, trophic in Suat Uğurlu Lake will remain a problem.